If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 45 = 23 + x Solving 45 = 23 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 45 + -1x = 23 + x + -1x Combine like terms: x + -1x = 0 45 + -1x = 23 + 0 45 + -1x = 23 Add '-45' to each side of the equation. 45 + -45 + -1x = 23 + -45 Combine like terms: 45 + -45 = 0 0 + -1x = 23 + -45 -1x = 23 + -45 Combine like terms: 23 + -45 = -22 -1x = -22 Divide each side by '-1'. x = 22 Simplifying x = 22
| 40=9/5c | | Y=7Sin(6x+5)+2Cos(3x-2) | | 5x-(-2x+1)=2 | | 2x+6+x+1=3(x-1)+6 | | 3x^2-8y^2=-5 | | 2/10➗3/100 | | 0=-18v^2+1476v-26600 | | 3(x-3)+4=2[-(x-5)-4(2x+1)] | | 4a^2+4a=-15 | | 4a^2+4=-15 | | 2x^1-1=0 | | 5x+60=5x | | 449/0.42= | | 16/5-20x=8 | | 2500+100x+x^2= | | log(5x+1)=1.2 | | y8/y3 | | 6+k^7=-2 | | 3x^3-5x-1=0 | | (36x^4+9)=0 | | 0.05(0.3x-0.06)= | | logx^729=3 | | 4n+5=2n+8 | | logx^36=2 | | 4y+49=27y+7 | | 4y+36=27y+7 | | 4.8x-4=4(1.2x-1) | | 4y+1636=27y+7 | | 8x-5x=x+8 | | 4y+25=27y+7 | | 4y+16=27y+7 | | y+2.4=7.33 |